Research and Implementation of a 1800°C Sapphire Ultrasonic Thermometer. (14th December 2017) - Liang, Haijian; Yang, Fengbao; Yang, Lu; Liu, Zhengguang; Wang, Gao; Wei, Yanlong; Xue, Hongxin
Abstract : A sapphire ultrasonic temperature sensor was produced in this study which possessed working stability, antioxidation properties, and small acoustic-signal attenuation. A method was developed to solve the problems of long periods (>0.5 h) and ultrahigh temperature (1800°C) in tests. The sensor adopted here had good sound transmission performance as well as the high thermal conductivity of sapphire single crystals (Al2 O3 ), as ultrasonic waveguides. The ultrasonic waveguide was produced by the method of the laser-heated pedestal growth (LHPG method). Calibration experiments in a high temperature furnace found that, at high temperatures and long exposure, sapphire ultrasonic temperature sensors had good stability and repeatability, and it survived in 1600°C for 360 min. This sapphire ultrasonic temperature sensor has potential for applications in aircraft engines where monitoring of high temperatures is very important.